1974
DOI: 10.1083/jcb.61.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bone Tissue in Culture From Isolated Bone Cells

Abstract: A system is described for the formation of bone tissue in culture from isolated rat bone cells. The isolated bone cells were obtained from embryonic rat calvarium and periosteum or from traumatized, lifted periosteum of young rats. The cells were cultured for a period of up to 8 wk, during which time the morphological, biochemical, and functional properties of the cultures were studied. Formation of bone tissue by these isolated bone cells was shown, in that the cells demonstrated osteoblastic morphology in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1
2

Year Published

1977
1977
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(49 citation statements)
references
References 24 publications
3
43
1
2
Order By: Relevance
“…Since both PTH and PGE2 were shown to increase ornithine decarboxylase activity (S6mjen et al, 1982b) and DNA synthesis (S6mjen et al, 1982a), it was the purpose of the present study to investigate whether trophic polypeptides are able to stimulate CK activity in bone cells. Preliminary reports of part of these results were presented at recent meetings (Kaye et al, 1984;S6mjen et al, 1984c Bone-cell cultures were prepared from calvaria of 19-20-day-old rat embryos (Binderman et al, 1974). Calvaria were excised and cells were released by digestion with trypsin/EDTA.…”
mentioning
confidence: 99%
“…Since both PTH and PGE2 were shown to increase ornithine decarboxylase activity (S6mjen et al, 1982b) and DNA synthesis (S6mjen et al, 1982a), it was the purpose of the present study to investigate whether trophic polypeptides are able to stimulate CK activity in bone cells. Preliminary reports of part of these results were presented at recent meetings (Kaye et al, 1984;S6mjen et al, 1984c Bone-cell cultures were prepared from calvaria of 19-20-day-old rat embryos (Binderman et al, 1974). Calvaria were excised and cells were released by digestion with trypsin/EDTA.…”
mentioning
confidence: 99%
“…the second of large multinucleated osteoclastlike cells, the third of fibroblast-like cells and the fourth of cells with intermediate characteristics between fibroblasts and osteoblasts. Although the four cell types persisted in subcultures, the percentage of osteoblast-like cells increased, asothers have reported [5][6][7][8]. Since there is no literature on the cytoskeletal organization in otosclerotic cells, the morphological investigation was completed by carrying out indirect immunofluorcsccnt studies to deter mine the localization and distribution of some of the more important cytoskeletal proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these cells are capable of collagen production in vitro but formation and calcification of bone matrix are rarely obtained. Recently, a number of investigators have reported calcification to occur in their bone cell cultures (2,3,18,19,27) . However, although these studies show matrix formation and calcification in bone cell cultures, they do not provide definite proof of the ability of bone cells in monolayer culture to produce calcified bone matrix; light microscope studies do not show convincingly the presence ofosteoblasts and bonelike structures (2,3,18,19,27), the organic matrix may differ from the bone matrix in vivo (3), and matrix formation and calcification also occur in cultures of skin fibroblasts, albeit to a lesser extent (27).…”
mentioning
confidence: 99%